OPTIMALISASI ZPT (ZAT PENGATUR TUMBUH) ALAMI EKSTRAK BAWANG MERAH (Allium cepa fa. ascalonicum) SEBAGAI PEMACU PERTUMBUHAN AKAR STEK TANAMAN BUAH TIN (Ficus carica) - Nurus Sofwan; Ovi Faelasofa Kusuma D; Achmad Heru Triatmoko; Siti Nurul Iftitah (Universitas Tidar, 2018)
Research of Optimizing Natural Growth Regulatory on Red Onion Extract (Allium cepa fa. Ascalonicum) as a Growth Root of Tin Crop Fruit Cultivation (Ficus carica) was a study which aims to utilize red onion extract as a trigger of root growth in the multiplication of tin fruit plants through stem cuttings. Utilization of onion extract in various concentrations were 0%, 0.5%, 1%, 1.5% and 2%. This study used the method of Randomized Complete Random Design (RAL) with the analysis of orthogonal polynomial quantitative data from 25 plant samples. The results showed that all treatments had an effect on the number and length of root of tin plant. The 1% concentration provides optimum results against the observed parameters compared to control and other treatments. Achievement of longest root long optimum point was at concentration 1.14% while the optimum root number was at concentration 1.07%.